STUDI LITERATUR KEPADA TIGA PENELITIAN CRM, DMO DAN IMPLIKASI MEDIA SOSIAL TERHADAP TRAVEL PLANNING - Irma Kharisma Hatibie (Tulisan Ilmiah Pariwisata (TULIP), 2018)
Social media is one of a tool that has the function to increase and increase promotion and marketing, including Tourism sector. However, this tool developing social media which is a part of daily life, has different and varied implications in each use; Use anyone to use social media. If we look at it from the user's perspective, random results will be obtained. Especially if the users are people from various ages, education, and culture. However, in some studies the use of social media can be constrained in terms of its benefits, especially for tourism promotion and marketing purposes. The main focus of this article discussion include; Whichever organization uses and uses social media, what strategies are implemented, and the implications of today's and future for the audience. If we only observing social media consisting only of a series of updated popular applications, then in this paper offers opinions about some substantial research on using social media as a method for analyzing tourism market segmentation, by taking samples in several countries, in the field of Tourism such as DMO (Destination Marketing Organisation), and what form of communication results from social customer relationships management (SCRM) through social media. This article was prepared using a literature study of three articles that discuss the urgency of social media issues. These three studies were appointed as a rationale for social media in the country